Evaluasi Kinerja Pada Mesin Casting Menggunakan Metode Overall Equipment Effectiveness di PT. Surya Toto Indonesia - Selamet Riadi; Syaiful Anwar (Universitas Bunda Mulia, 2019)
PT. Surya Toto Indonesia is a company engaged in ceramic sanitary wares and plumbing hardware. One of the company’s problems regarding production is high breakdown times. This breakdown causes a decrease in engine speed, even farther affects the output that has been previously planned. This study aims to measure the value of overall equipment effectiveness (OEE), to know the factors lead to decreased effectiveness through Six Big Losses and to provide recommended improvements. This study begins by measuring the value of OEE, then identifying the Six Big Losses and analyzing the causes of the problem of decreasing machine effectiveness. OEE calculation components are availability, performance efficiency and rate of quality. The results showed that the percentage of Availability Value calculation ranged between 90%-96%, while the percentage of Performance Efficiency value calculation ranged between 37%-64%, then the result of the calculation of Rate of Quality 96.7%-99.8%. Then obtained the percentage of the calculation value of OEE which ranged between 35%-59%, with an average value of OEE in January to December 2017 that is equal to 47%. This value of effectiveness is relatively low because the standard value of OEE for world-class is 85%. While the factor of Six Big Losses most influential on the low effectiveness of the machine is Reduced Speed Losses with a total time loss of 11691 minutes.